Germany : Financial Sector Assessment Program-Systemic Liquidity and Bank Funding-Technical Notes. (IMF Staff Country Reports; Country Report ;, 2016)
This paper focuses on the current state of the principal markets for nondeposit based funding for German financial institutions. A key finding is that although the current level of liquidity of the banking system is abundant, underpinned by active central bank support, the resilience of liquidity in some bank funding markets appears weaker than in the past. The financial system is dominated by banks and is generally sound and robust to shocks. The German banking system consists of a large number of banks in three main pillars: private commercial banks, public sector banks, and cooperative banks (accounting for 39 percent, 27 percent, and 14 percent, respectively of total banking system assets).